Global, regional and national burden of deciduous dental caries from 1990 to 2021: analysis of risk factors and prediction of trends in 2035 - Yang, Hong; Feng, Yong; Xiao, Li-Yuan; Wang, Kai-Mei; Feng, Hong-Chao (Frontiers in Dental Medicine, 2025)
Background/aimEarly childhood caries (ECC) is one of the most prevalent global oral health issues in children under five years old, significantly impacting their overall health and quality of life. This study aimed to analyze the global, regional, and national burden of ECC from 1990 to 2021, identify associated risk factors, and predict trends through 2040. It further examined the influence of socio-demographic factors, sex, and age on ECC incidence and prevalence.Patients and methodsData from the Global Burden of Disease (GBD) 2021 database were analyzed using Bayesian Meta-Regression models to estimate ECC incidence, prevalence, and years lived with disability (YLDs) across 204 countries and regions. Socio-Demographic Index (SDI) levels, sex, and age-specific trends were assessed. Age-standardized rates and estimated annual percentage changes (EAPCs) were calculated. Predictive models, including ARIMA, were developed to forecast future trends.ResultsBetween 1990 and 2021, ECC incidence and prevalence showed modest declines globally, with significant variations across SDI regions. High SDI regions exhibited the lowest burden due to effective public health measures, while medium and low SDI regions faced persistent challenges. Sex disparities were observed, with males showing slightly higher rates than females. Children aged 5–9 years bore the highest burden of ECC. Predictions for 2040 indicate a potential rebound in ECC incidence in low and medium SDI regions without targeted interventions.ConclusionThis study highlights the substantial burden of ECC, particularly in under-resourced regions, and underscores the need for tailored public health strategies. Effective prevention, improved healthcare access, and education are critical to reducing ECC burden globally, ensuring better oral health outcomes for children, and addressing disparities across socio-economic, sex, and age groups.